Chinese Company QuantumCTek Analysis and Improvement: Business Plan Case Study - Lyu, Wenbo; Min, Chenxi (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Quantumctek is mainly engaged in the research and development, production, sales and technical services of quantum secure communication products. It is the quantum equipment provider of the world's first long-distance quantum secure communication trunk line "Beijing-Shanghai Trunk Line", "National Wide Area Quantum Backbone Network (Phase I)" and other projects, and participated in the construction of "Micius" quantum satellite secure communication ground station. Google's Gidney and Ekera have shown how a quantum computer could use 20 million qubits to break RSA encryption, now the most widely used, at 2048 bits. They demonstrated that such a device could be in just eight hours. In the future, the company must build a platform, continue to open API ports to market forces, gradually establish a complete industrial value chain, and realize the high growth of network effects as soon as possible.